Social individual circumstances of the personalized medicine in prevention of the family of fetus anomalies (review of international experience) - A. S. Kiselev (Сеченовский вестник, 2014)
In this work the brief classification of the main of family of fetus anomalies with a correlation of scientic advances in genetics, molecular biology, embryology. The article makes it possible to characterize the current state of development the personalized medicine in the prevention of family of fetus anomalies.